2016
DOI: 10.1176/appi.ps.201500306
|View full text |Cite
|
Sign up to set email alerts
|

Enrollment and Service Use Patterns Among Persons With Severe Mental Illness Receiving Expedited Medicaid on Release From State Prisons, County Jails, and Psychiatric Hospitals

Abstract: Expediting Medicaid benefits for persons with severe mental illness was associated with increased enrollment and outpatient mental health service use in the 90 days after release from state prisons, county jails, and psychiatric hospitals in Washington State.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Control subjects were retained if they enrolled in Medicaid through some mechanism other than the expedited program; 82 people who received an expedited Medicaid referral more than 31 days after release were recoded as controls rather than treated individuals. These may be individuals who deferred finalizing their Medicaid enrollment or who were referred to the expedited program during a subsequent hospitalization or stay in the criminal justice setting . These 82 individuals had substantially higher rates of subsequent contact with the Department of Corrections ( P < 0.001) or jail ( P < 0.002) and a greater number of arrests ( P < 0.001) in the 12 months post–index release than did other study subjects, making a referral after a subsequent re‐incarceration a likely explanation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Control subjects were retained if they enrolled in Medicaid through some mechanism other than the expedited program; 82 people who received an expedited Medicaid referral more than 31 days after release were recoded as controls rather than treated individuals. These may be individuals who deferred finalizing their Medicaid enrollment or who were referred to the expedited program during a subsequent hospitalization or stay in the criminal justice setting . These 82 individuals had substantially higher rates of subsequent contact with the Department of Corrections ( P < 0.001) or jail ( P < 0.002) and a greater number of arrests ( P < 0.001) in the 12 months post–index release than did other study subjects, making a referral after a subsequent re‐incarceration a likely explanation.…”
Section: Methodsmentioning
confidence: 99%
“…In this analysis, we find that it is also highly associated with the receipt of timely mental health services or that it serves as a strong instrument, with linear F ‐statistics well over 100 in all models on the full sample and over 20 in all subsample models, controlling for 59 additional exogenous variables. The primary reason for lack of referral was due to capacity constraints in identifying and recommending individuals to the program, which was just started in 2006 . We believe that referral to expedited Medicaid is not otherwise associated with criminal justice use except through the receipt of mental health treatment, once we control for a large number of baseline criminal justice and history of mental health services variables that occurred prior to the index incarceration.…”
Section: Methodsmentioning
confidence: 99%
“…In state prisons, corrections mental health staff first identified offenders with mental illness, assisted them with Medicaid applications, and referred them to Community Service Offices where offenders had to appear following release for approval determinations. Further details about the policy context are available elsewhere (30). …”
Section: Methodsmentioning
confidence: 99%
“…A pilot study in three Oklahoma prisons found that a discharge planning program for inmates with serious mental illness increased both Medicaid enrollment and mental health service use by 16% within 90-days of release (29). Our prior research on prisons in Washington State also showed that expediting Medicaid for offenders with severe mental illness was associated with increased Medicaid enrollment by 15% and increased outpatient mental health service use by 13% in the 90 days following release from state prison (30). However, no prior research on state prisoners has addressed the question of whether expediting Medicaid benefits actually leads to reduced criminal recidivism for offenders with severe mental illness.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation